The Emancipation Proclamation - Heinrichs, Ann (Minneapolis, MN Compass Point Books, 2001)
Looks at the political and moral issues that caused President Lincoln to issue the 1863 document that freed many slaves, and at the immediate and long-term consequences of his action.
Keywords: Emancipation Proclamation; Lincoln, Abraham, 1809-1865.; Slavery - History; United States - History - Civil War, 1861-1865.; African Americans - History